SOCIO-ECONOMIC ASSESSMENT OF HUMAN RESOURCE MANAGEMENT EFFECTIVENESS UNDER UNCERTAINTY - Mykhailo Dreichuk; Yosyf Sytnyk (Three Seas Economic Journal, 2025)
The purpose of this paper is to develop a comprehensive conceptual framework for assessing the effectiveness of human resource management (HRM) under conditions of uncertainty. The study focuses on integrating socio-economic indicators into a structured evaluation model that reflects not only financial results but also social outcomes such as employee well-being, engagement, and adaptability. By addressing the limitations of traditional HRM evaluation methods, which often prioritize efficiency and cost control, the article proposes a more balanced and resilient approach suited for volatile environments. Methodology. The study adopts a conceptual and analytical approach, relying on an extensive review of contemporary academic literature and international standards for human capital reporting, including ISO 30414:2018. The authors synthesize findings from empirical and theoretical studies on HRM performance, high-commitment work systems, sustainable HRM, and human capital risk management. The research does not involve primary data collection or empirical testing. Instead, the framework is constructed on the basis of recognized academic principles and comparative analysis of existing evaluation models. The methodology also draws upon strategic management concepts, including dynamic capabilities and stakeholder theory, to ensure that the proposed framework is adaptive and aligned with organizational objectives and risk factors. Results. The main output of the research is a multi-dimensional analytical framework for evaluating HRM effectiveness under conditions of uncertainty. This framework incorporates both economic metrics (e.g., productivity, return on investment in human capital, turnover costs) and social indicators (e.g., employee satisfaction, stress levels, adaptability, organizational commitment). The evaluation process is structured into key stages: identification of uncertainty factors, goal alignment with stakeholders, selection and weighting of indicators, and feedback-driven adaptation. The framework is designed to be flexible, scalable, and applicable across different industries. It enables decision-makers to monitor HRM performance over time, adjust HR strategies proactively, and integrate human capital metrics into broader organizational risk assessments. Practical implications. The framework can serve as a practical tool for HR professionals and organizational leaders seeking to manage and evaluate HRM performance in unpredictable conditions such as war, crisis, recession, or digital transformation. It supports the design of HR dashboards, enhances human capital reporting, and fosters data-informed decisions that safeguard both employee welfare and long-term business goals. The article also opens a pathway for future empirical studies, particularly on how socio-economic indicators can be customized and weighted in sector-specific or country-specific settings. Value / originality. The originality of this research lies in its socio-economic approach to HRM effectiveness evaluation in uncertain environments. Unlike traditional models that isolate financial outcomes or internal process metrics, this framework acknowledges the interdependence of social and economic dimensions. It positions employees as key stakeholders and contributors to resilience, innovation, and sustainable performance. By proposing a balanced, human-centered framework, the article responds to global calls for responsible HRM and contributes to the advancement of strategic HRM practices suitable for dynamic and high-risk contexts, particularly in emerging economies.